The million-dollar, one-person business : make great money, work the way you like, have the life you want - Pofeldt, Elaine (Lorena Jones Books, 2021)
"By harnessing new, easy-to-use technologies that help them find customers around the world, everyday people are starting meaningful businesses that offer a high-paying alternative to a corporate career. In this updated edition of THE MILLION-DOLLAR, ONE-PERSON BUSINESS, learn tactics you can apply today from real people who are earning $1 million a year on their own terms"--